Factors associated with an unsuccessful fast-track course following minimally invasive surgical mitral valve repair. (7th September 2022) - Van Praet, Karel M; Kofler, Markus; Hirsch, Solveig; Akansel, Serdar; Hommel, Matthias; Sündermann, Simon H; Meyer, Alexander; Jacobs, Stephan; Falk, Volkmar; Kempfert, Jörg
Abstract: OBJECTIVES: Analyses of fast-track (FT) processes demonstrated that low-risk cardiac surgical patients require minimal intensive care, with a low incidence of mortality or morbidity. We investigated perioperative factors and their association with fast-track failure (FTF) in a retrospective cohort study of patients undergoing minimally invasive mitral valve surgery. METHODS: Patients undergoing minimally invasive surgical mitral valve repair for Carpentier type I or type II mitral regurgitation between 2014 and 2020 were included in the study. The definition of FTF consisted of >10 h mechanical ventilation, >24 h intensive care unit stay, reintubation after extubation and re-admission to the intensive care unit. Multivariable logistic regression analysis enabled the identification of factors associated with FTF. RESULTS: In total, 491 patients were included in the study and were analysed. Two hundred and thirty-seven patients (48.3%) failed the FT protocol. Multivariable logistic regression analysis showed that a New York Heart Association classification ≥III [odds ratio (OR) 2.05; 95% confidence interval (CI) 1.38–3.08; P < 0.001], pre-existing chronic kidney disease (OR 2.03; 95% CI 1.14–3.70; P = 0.018), coronary artery disease (OR 1.90; 95% CI 1.13–3.23; P = 0.016), postoperative bleeding requiring surgical revision (OR 8.36; 95% CI 2.81–36.01; P < 0.001) and procedure time (OR 1.01; 95% CI 1.01–1.01; P < 0.001) were independently associated with FTF. CONCLUSIONS: Factors associated with FTF in patients with Carpentier type I and II pathologies undergoing minimally invasive mitral valve repair are a New York Heart Association classification III–IV at baseline, pre-existing chronic kidney disease and coronary artery disease. Postoperative bleeding requiring rethoracotomy and procedure time were also identified as important factors associated with failed FT. Abstract : Several institutions have improved their expertise in the field of minimally invasive cardiac surgery (MICS) as new technologies and approaches have developed [1].